TRANSDERMAL PATCH PILIS FROM TURMERIC RHIZOME AND BLACK SEEDS FOR TREATMENT BASED ON ETHNOPHARMACY - Susanto, Nindita Clourisa Amaris; Sawitri, Arinda Handiyah; Muslimah, Intan (BRIN - Badan Riset dan Inovasi Nasional, 2024)
Pilis, a traditional product containing various herbal ingredients, is currently less desir-able due to its impractical and unfashionable method of application. Pilis is used to treat dizziness, pain, eye fatigue, encephalitis in children, fever, and to aid recovery for mothers after childbirth. However, pilis also carries risks related to uncontrolled dosage and contamination, particularly from chemical or heavy metal pollutants, which may cause toxic reactions. To mitigate these risks, pilis should be used in recommended doses and produced under clean and safe conditions. This research aimed to provide the innovation of patches as an alternative treatment to increase attractiveness and control the active substances released and delivered for a long time. Transdermal patches are made from a combination of turmeric and black seed containing flavonoid active metabolite compounds, namely curcumin, carotenoids, quercetin, kaempferol, and apigenin. The combination has a synergistic effect that can increase total flavonoid levels and the therapeutic effect of pilis. The method used in this research was litera-ture review and data analysis. The results showed the effect of transdermal patch pilis from the combined extracts added to the formula in vitro and in vivo using animal tests. In conclusion, transdermal patch pilis has prospects as a topical treatment based on the combination of an active delivery system with a patch and metered dose system.